THEORY OF FINANCIAL BEHAVIOR IN THE CONCEPT OF SCOPING REVIEW: PERSPECTIVE OF EXPORT CRAFTS MSMEs - Ratnawati; Ayu Agus Tya Ningsih; Ismatud Diyanah (Formosa Journal of Multidisciplinary Research, 2024)
Financial behaviour refers to an individual's approach to handling, overseeing, and utilising financial assets. Prior studies have examined the correlation between financial literacy and financial outcomes. This scoping review aims to systematically identify and analyse the current body of research examining financial literacy's impact on financial performance. The primary steps involved in a scoping review include (1) formulating research inquiries, (2) locating pertinent studies, (3) selecting studies, (4) organising and recording data, and (5) assembling, summarising, and presenting findings. From 2012 to 2021, a scoping analysis reveals that most research acknowledges the impact of financial literacy on the success of micro, small, and medium enterprises (MSMEs). According to Mira & Indrayani (2020), Barte, Rhenozo (2012), and Eke & Raath (2013), there is no evidence to support the idea that financial literacy has an impact on the financial performance of MSMEs.